Α‐Quaternary Mannich Bases through Copper‐Catalyzed Amination‐Induced 1, 2‐Rearrangement of Allylic Alcohols. Issue 41 (3rd July 2017) - Weng, Wei‐Zhi; Sun, Jian‐Guo; Li, Ping; Zhang, Bo
Abstract: A novel copper‐catalyzed amination‐induced 1, 2‐rearrangement reaction of allylic alcohols has been developed under simple and mild conditions. The commercially available N ‐fluorobenzenesulfonimide (NFSI) is employed as an amination reagent. In this transformation, not only alkyl, but also aryl substituents can efficiently undergo 1, 2‐carbon atom migration, thereby providing an efficient and powerful route to prepare a wide range of α‐quaternary Mannich bases. The reaction features a broad substrate scope, operational simplicity, and excellent practicality. Abstract : A novel copper‐catalyzed amination‐induced 1, 2‐rearrangement reaction of allylic alcohols has been achieved under simple and mild conditions. This transformation exhibits a broad substrate scope and good functional group tolerance. A variety of Mannich bases containing an α‐quaternary center are readily prepared in moderate to excellent yields using the title reaction.